(untitled) (Indian Journal of Public Health Research & Development, 2021)
Nutritional status is an important influence on overall health and wellbeing of a population. One of the vulnerable group is tribal population. The main tribe found in Karnataka is Soliga tribal community, majority of them have low economic status. Hence, malnutrition can be the most common condition arising in this community due to inadequate intake of dietary nutrients. In this purposive, free-living study, the detailed information on the population distribution, nutritional status, nutrient intake of Soliga community (30-65 years) were assessed using standardised questionnaires which included health and lifestyle related Knowledge, Attitude and Practice (KAP) questions. Anthropometric measurements were assessed using standard method. The dietary and nutrient intakes were collected using food frequency questionnaires and 24-hour dietary recall method. The tribal colonies mainly depended on minor forest produce and manual labour for livelihood, and majority of the study population were economically deprived. The BMI was normal in men, whereas women were undernourished. The 24-hour dietary recall data revealed that the subjects followed 2 major meals, about 97% population consumed mixed type of diet, the intake of macronutrients was lower than the recommended dietary allowances. The KAP survey revealed that subjects possessed good health and hygiene related knowledge and attitude, but poorly practiced. Constant monitoring of nutritional status and bridging the gaps in nutritional KAP of the tribal population can provide early warning of any deterioration in their health and nutritional status, hence facilitating effective planning and implementation of nutrition interventions in this unique population.